2022
DOI: 10.1093/nar/gkac569
|View full text |Cite
|
Sign up to set email alerts
|

Short LNA-modified oligonucleotide probes as efficient disruptors of DNA G-quadruplexes

Abstract: G-quadruplexes (G4s) are well known non-canonical DNA secondary structures that can form in human cells. Most of the tools available to investigate G4-biology rely on small molecule ligands that stabilise these structures. However, the development of probes that disrupt G4s is equally important to study their biology. In this study, we investigated the disruption of G4s using Locked Nucleic Acids (LNA) as invader probes. We demonstrated that strategic positioning of LNA-modifications within short oligonucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Consistently with our biophysical and biochemical data, we found that short LNA-modified probes significantly enhanced c-KIT1 geneexpression, whereas this effect was not observed when the isosequential unmodified DNA probe was used (Figure 6). 69 Taken together, our studies demonstrated that short LNA-modified oligonucleotides are viable chemical-biology tools that can individually target and disrupt specific G4s both in vitro and in cells. This opens-up new possibilities of the use of these sequence-specific probes to study the biological effect of disrupting individual G4s (rather than using unspecific small-molecules).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 56%
See 3 more Smart Citations
“…Consistently with our biophysical and biochemical data, we found that short LNA-modified probes significantly enhanced c-KIT1 geneexpression, whereas this effect was not observed when the isosequential unmodified DNA probe was used (Figure 6). 69 Taken together, our studies demonstrated that short LNA-modified oligonucleotides are viable chemical-biology tools that can individually target and disrupt specific G4s both in vitro and in cells. This opens-up new possibilities of the use of these sequence-specific probes to study the biological effect of disrupting individual G4s (rather than using unspecific small-molecules).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 56%
“…6). 69 Taken together, our studies demonstrated that short LNAmodified oligonucleotides are viable chemical-biology tools that can individually target and disrupt specific G4s both in vitro and in cells. This opens-up new possibilities of the use of these sequence-specific probes to study the biological effect of disrupting individual G4s (rather than using unspecific small-molecules).…”
Section: Use Of Lna Probes To Disrupt G4smentioning
confidence: 56%
See 2 more Smart Citations
“…However, given the multiple roles of G4s in gene regulation their non-specific targeting throughout in the genome is clearly not satisfactory. The current development of new strategies able to target G4 structures within a given sequence [171,182] would certainly open new opportunities, by providing therapeutic means to target a single S region and then inhibit CSR to a single Ig gene with minimal side effects.…”
Section: Pharmacological G4 Targeting and Potential Implications For ...mentioning
confidence: 99%